Pengaruh Kualitas Pelayanan dan Profesionalisme Pegawai Terhadap Kepuasan Pelayanan E- KTP di Kecamatan Tunjungan Kabupaten Blora - Christine Diah Wahyuningsih; Feby Dwi Ismawati (Universitas 17 Agustus 1945, 2025)
Population administration services in each sub-district are a form of public service carried out by the Government in terms of serving the population administration needs of the local community. The problem in this study is to find the effect of service quality and employee professionalism on the satisfaction of the community using e-KTP services in Tunjungan sub-district, Blora Regency, while the objectives to be achieved are to find out and analyze the effect of service quality and employee professionalism on the satisfaction of the community using e-KTP services in Tunjungan sub-district, Blora Regency, then the population in this study was the community of Tunjungan sub-district as many as 45 people who were selected using accidental sampling techniques (based on coincidence) which were considered appropriate for the type of research while the sample was selected by purposive sampling (based on special characteristics) of the community who came to the Tunjungan sub-district office and had applied for e-KTP services. The results of the analysis concluded that there is a significant influence between Service Quality and Employee Professionalism on the satisfaction of the community of Users of e-KTP Making Services in Tunjungan District, Blora Regency, this is based on the results of the Determination Coefficient analysis where the calculation results were 63.5%, this is based on the existing interval, namely at the interval 60.00 -79.99% influential, while 36.5% of the satisfaction of the Community of Users of e-KTP Making Services is influenced by other factors such as Sub-district Leadership, Organizational Culture, Work Environment, Work Facilities, etc.